The Influence Of Product Quality, Price, And Social Media Promotion On Purchase Decisions At Online Thrift Shops (Thriftguys) - Naufal, Aldi; Sudaryo, Yoyo; Dayona Ismail, Gurawan (Green Publisher Indonesia, 2025)
This study aims to analyze the influence of product quality, price, and social media promotion on consumer purchasing decisions at the online thrift store Thriftguys. The research employed a quantitative approach with a descriptive-verificative method, involving 96 respondents who had made online purchases. Data were collected through a five-point Likert scale questionnaire and tested for validity and reliability. Multiple linear regression analysis was used to examine the partial and simultaneous effects of the independent variables on the dependent variable. The results indicate that product quality, price, and social media promotion have a significant influence on consumer purchasing decisions, both individually and collectively. A determination coefficient of 52.1 percent suggests that these three variables jointly provide a substantial explanation for purchasing decisions. These findings offer a practical basis for thrift business owners to develop more effective marketing strategies by enhancing product quality, setting competitive prices, and utilizing engaging social media promotions.